Helicobacter pylori Infection Maybe a Risk Factor for Cardiac Syndrome X - Zhang, Dong-Hong; Yuan, Chen; Wang, Bei-Bei; Dong, Xin-Jiang; Lv, Shu-Ping; Li, Fei-Hong; Hou, Zhen-Xiu; Liu, Xiao-Li; Chen, Kang (Frontiers in Cardiovascular Medicine, 2022)
Purpose Cardiac syndrome X (CSX) is a condition with normal coronary angiography but angina pectoris. Chronic inflammation caused by Helicobacter pylori (H. pylori) infection may play a pathogenic role in CSX. Therefore, we conducted a meta-analysis to explore the relationship between H. pylori infection and risk of CSX. Methods A systematic search in the Web of Science, Medline, Embase and Chinese databases (CNKI and Wanfang) was conducted up to October 2021. Articles on the association between H. pylori infection and the risk of CSX were included and were analyzed by R software (version 4.1.0). Results Ten case-control studies involving 703 CSX patients and 731 healthy controls were included. H. pylori infection was associated with an increased risk of CSX (OR: 8.29, 95% CI: 4.64–14.82). We also found a significant association in those 25–40 years of age (OR: 1.34, 95% CI: 1.04–1.72), those 40–50 years of age (OR: 11.27, 95% CI: 4.29–29.61), those over 50 years of age (OR: 7.18, 95% CI: 3.59–14.36), those in developing countries [Iran (OR: 12.99, 95% CI: 8.61–19.60) and China (OR: 5.14, 95% CI: 3.09–8.56)]. However, this association was not apparent in a developed country [Italy (OR: 0.93, 95% CI: 0.37–2.33)]. Conclusions Our study suggested a possible association between H. pylori infection and the risk of CSX. Its pathogenicity is stronger in middle-aged individuals and some developing countries. However, more studies are needed to further investigate whether early eradication of H. pylori can reduce the incidence rate of CSX, especially in middle-aged individuals and some developing countries.